The Level of Reading Interest and Speed Reading of Science, Technology, Engineering, and Mathematics Learners: A Correlational Study - Morong, Nunilon Harvey H.; Congayo, Rhain Kenneth; Benedicto, Sharlene O.; Esparcia, Michaella Angela A.; Oraca, Ella Via; Abal , George II; Cabe, Alphil Christian C. (Future Science / FSH-PH Publications, 2024)
Speed reading is a requisite skill in reading comprehension among adolescent learners. It allows them to process information quickly and meaningfully. Since reading has been a major concern of the Philippine education despite efforts exerted for years, this study aimed to determine whether reading interest itself among adolescent learners correlates with speed reading, particularly grade 11 science, technology, engineering, and mathematics (STEM) learners from a private university in City of Koronadal, South Cotabato. A descriptive-correlational design was used in the study, utilizing an adopted survey questionnaire to assess the level of reading interest and a reading comprehension test to assess the speed reading of the respondents. The data were analyzed using descriptive statistics such as weighted mean to describe the level of reading interest; an effective reading rate (EER) to assess speed reading; and a Pearson correlation coefficient (r) to determine the relationship between reading interest and speed reading. It was found that the level of reading interest of the respondents was high; their speed reading was classified as above average; and thus, there was a high positive correlation between the level of reading interest and speed reading among the respondents, signifying that efforts should be made as well toward intensifying love for reading among Filipino learners.